2015
DOI: 10.1039/c5ra06680h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, photoluminescence and Judd–Ofelt analysis of red LiGd5P2O13 : Eu3+ phosphors for white LEDs

Abstract: A series of LiGd 5 P 2 O 13 : Eu 3+ phosphors with a red-emitting band centered at 622 nm were synthesized by a high temperature solid-state reaction method. Structure-luminescence correlation, concentration quenching and thermal stability of the LiGd 5 P 2 O 13 : Eu 3+ phosphors were studied combined with XRD, PL/PLE spectra as well as temperature-dependent PL and decay curves. The optimum concentration of Eu 3+ doped in the LiGd 5 P 2 O 13 is 20 mol%, and the corresponding concentration quenching mechanism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…However, the Ω 4 value is insensitive to the coordination environment of Eu 3+ ions and dependent on the electron density of the surrounding ligands . Our Ca 8 ZnLa 0.5 Eu 0.5 (PO 4 ) 7 phosphor exhibited smaller Ω 2 and Ω 4 values than reported previously for other red phosphors, such as LiGd 5 P 2 O 13 : Eu 3+ and Ba 5 Gd 8 Zn 4 O 21 : Eu 3+ . This indicates that our Ca 8 ZnLa 0.5 Eu 0.5 (PO 4 ) 7 phosphor exhibits reduced covalent character/electron density around its Eu 3+ ions.…”
Section: Resultsmentioning
confidence: 47%
“…However, the Ω 4 value is insensitive to the coordination environment of Eu 3+ ions and dependent on the electron density of the surrounding ligands . Our Ca 8 ZnLa 0.5 Eu 0.5 (PO 4 ) 7 phosphor exhibited smaller Ω 2 and Ω 4 values than reported previously for other red phosphors, such as LiGd 5 P 2 O 13 : Eu 3+ and Ba 5 Gd 8 Zn 4 O 21 : Eu 3+ . This indicates that our Ca 8 ZnLa 0.5 Eu 0.5 (PO 4 ) 7 phosphor exhibits reduced covalent character/electron density around its Eu 3+ ions.…”
Section: Resultsmentioning
confidence: 47%
“…Otherwise, the relative intensity of every lines especially the 5 D 0 ‐ 7 F 1 and 5 D 0 ‐ 7 F 2 transitions was highly relied on the crystal environment of lattice around Eu 3+ ions. It was well‐known that the ratio ( R ) between the 5 D 0 ‐ 7 F 2 / 5 D 0 ‐ 7 F 1 transitions was the effective way to detect the symmetry around Eu 3+ ions . 5 D 0 ‐ 7 F 2 transition was a kind of electronic transition which was very sensitive to Eu 3+ site symmetry in the host, while the 5 D 0 ‐ 7 F 1 magnetic dipole transition was insensitive to site symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the transitions from 5 D 0 to 7 F 2 and 7 F 4 levels are electric dipole in character. 5 D 0 ‐ 7 F 3 transition is forbidden from both electric and magnetic dipole considerations . Due to these transitions, Eu 3+ ions could be regarded as not only the activators but also the tools to examine the symmetry of lattice.…”
Section: Introductionmentioning
confidence: 99%
“…5, the BEB:0.3Lu 3+ phosphor spanned more red region than Y 2 O 2 S:Eu 3+ phosphor, and the integrated emission intensity of BEB:0.3Lu 3+ was about 3.25 times higher than that of Y 2 O 2 S:Eu 3+ . In addition, we also calculated the color purity of BEB:0.3Lu 3+ phosphor by using the following formula: 62 64,65 These results demonstrated that BEB:0.3Lu 3+ red phosphor may have much potential application for WLEDs.…”
Section: Luminescence Properties Of Beb:xlu 3+mentioning
confidence: 87%